2020
DOI: 10.3390/scipharm88040058
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 Inhibitor, Neuroprotective, and Neuritogenic Activities of Melatonin Derivatives

Abstract: Alzheimer’s disease (AD) is a common chronic neurodegenerative disorders. Melatonin (MLT) has been reported to be neuroprotective agent, and its modified structures exhibit potent antioxidant and anti-inflammation activities. Therefore, the activity of MLT and its derivatives against AD was investigated. Herein, the targeted enzymes, such as β-secretase (BACE1) and acetylcholinesterase (AChE), as well as the neuroprotective and neuritogenic effects on P19-derived neurons were evaluated. All the derivatives (1–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…Its binding energy to other binding regions within the enzyme ranges from −6.12 to 7.10 kcal/mol with favorable fitness scores ( Figure 6 ). The interaction of Thr232 and flap region residues buttress previous molecular docking prediction of compound 1 binding pose [ 37 ]. To give a clearer picture of the stability of compound 1 interaction to BACE1 at the different binding subsites, we simulate each complex ( Figure 6 ) using the amber force field.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Its binding energy to other binding regions within the enzyme ranges from −6.12 to 7.10 kcal/mol with favorable fitness scores ( Figure 6 ). The interaction of Thr232 and flap region residues buttress previous molecular docking prediction of compound 1 binding pose [ 37 ]. To give a clearer picture of the stability of compound 1 interaction to BACE1 at the different binding subsites, we simulate each complex ( Figure 6 ) using the amber force field.…”
Section: Resultsmentioning
confidence: 96%
“…Besides, Pietro et al’s (2017) study of conformational ensemble and binding mode analysis of some multisite inhibitors using MD and docking method [ 36 ], studies that explore multisite targeting of BACE1 towards drug design for AD are still scarce. In this study, we selected compounds ( Figure 4 ) proposed by different authors [ 28 , 29 , 30 , 31 , 37 , 38 , 39 , 40 , 41 ] as potent BACE1 allosteric inhibitors for some computational experiments. Docking analysis revealed that these compounds bind at allosteric sites but are highly stable at the active site.…”
Section: Introductionmentioning
confidence: 99%
“…The P19 embryonal carcinoma cell is a pluripotent stem cell line that can be differentiated into cholinergic neurons by all transretinoic acids [ 27 , 28 , 29 ]. The P19-derived neurons exhibit many characteristics of mature CNS neurons, containing neurotransmitter acetylcholine [ 28 ], which can be used as a model to evaluate neurotoxicity and neuroprotective activity [ 29 , 30 , 31 , 32 , 33 ]. In the present study, neurotoxicity assays were performed prior to neuroprotective activity assays, with test compounds at various concentrations of 1 to 10 4 nM to evaluate nontoxic concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, an in silico study predicted that the N1 -position lipophilic-substituted melatonin derivative ( N -(2-(1-4-bromobenzoyl-5-methoxy-1H-indol-3-yl)ethyl) acetamide, BBM) could not be metabolized by CYP1A2, which prolonged its half-life compared with melatonin [ 22 ]. In contrast, while another melatonin derivative with a 4-bromobenzoyl amide substitution at the N -acyl side chain (4-bromo- N -(2-(5-methoxy-1H-indol-3-yl)ethyl)benzamide, EBM) was predicted to be a substrate of CYP1A2, it displayed a potent antioxidant and neuroprotective effect [ 20 , 23 ]. Fan et al [ 24 ] also reported that N -salicyloyl tryptamine derivatives are potential anti-neuroinflammation agents that act by decreasing the production of proinflammatory mediators, NO, PGE 2 and TNF-α.…”
Section: Introductionmentioning
confidence: 99%